The Vayots Dzor Project (VDP): a preliminary overview of the first three years’ activities (2016-2018) - Gasparyan, Boris; Dan, Roberto; Petrosyan, Artur; Vitolo, Priscilla; Haydosyan, Hayk; Adigyozalyan, Ani; Azizbekyan, Hayk; Azatyan, Karen; Zecchi, Chiara; Moradi, Ghasem; Saccone, Tommaso; Bonfanti, Annarita Stefania; et al. (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
The Vayots Dzor Project (VDP) is an Armenian-Italian archaeological research project involving both survey and excavation activities, conducted in accordance with an agreement between IAE NAS RA (Institute of Archaeology and Ethnography NAS RA) and ISMEO-International Association of Mediterranean and Oriental Studies, co-funded by IAE NAS RA, Gfoeller Renaissance Foundation of USA, ISMEO and MAECI (Italian Ministry of Foreign Affairs and International Cooperation). The work is carried out in cooperation with the Yeghegnadzor Regional Museum. The project started in summer 2016, after a preliminary visit to the region – renowned for its vineyards and high-quality wine production – in 2015, with a view to its archaeological exploration. It is particularly focused on the investigation of the area surrounding the valleys of the River Arpa and its tributaries.